Appropriating the Past: Pageants, Politics, and the Diamond Jubilee of Confederation - Cupido, Robert (Journal of the Canadian Historical Association / Revue de la Société historique du Canada)

(untitled) (The Canadian Historical Association/La Société historique du Canada, 1998)
AbstractThis paper explores the relationship between public commemoration and the construction of social and political identity in the period between the wars, through a case study of the historical pageants that played such a conspicuous part in the celebration of the Diamond Jubilee of Confederation in 1927. Nationalist elites in Ottawa attempted to exploit pageantry for nation-building purposes by disseminating selective images of the past, conforming to the officially approved themes of material progress, social harmony and political unity. At the local level, historical pageants were used to define and celebrate the community's links to the past, present and future, the contribution of different social groups to its development, and its relationship to the larger nation. By organizing and participating in the pageants and other civic rituals of the Jubilee year through their networks of voluntary associations, middle-class women consolidated their public role as guardians of collective memory and historical tradition. And for a number of important groups-French-Canadian nationalists, British-Canadian imperialists, European immigrants and Native people, among others-a commemorative occasion intended to generate a common national consciousness ironically provided opportunities to affirm and celebrate competing sources of group loyalty and identity, through the use of historical representations that subverted the aims of federal organisers.